Orphans Deserve Attention: Financial Reporting in the Missing Months When Corporations Change Fiscal Year - Du, Kai; Zhang, X. Frank (The Accounting Review, 2013)
ABSTRACT We examine firms' financial reporting practices during the missing months that are induced by fiscal year changes and not covered by regular quarters. We find that firms tend to report much lower income for the missing months than for adjacent quarters, mainly by recording higher operating expenses. We also find that managers have various incentives to manage earnings. Executive compensation is not tied to firm performance in the transition period as it is in adjacent fiscal years. Growth firms, firms with poor stock returns, and firms with weak external and internal monitoring tend to manage earnings more. Finally, we find that firms are more likely to meet or beat earnings targets in the subsequent quarter by reporting lower income in the missing months. Investors and analysts perceive the earnings surprise to be less persistent in the quarter after than in the quarter before the missing months. Data Availability: Data are available from sources identified in the paper.